Wide Range Controllable Direction Single Emission Peak Microstructured Lasers Array - Yibo Yang; Zheng Wang; Yufei Wang; Sidra Farouk; Zhimin Ji; Xiuyan Sun; Pengfei Wang; Xuliang Zhou; Jiaoqing Pan; Yanmei Su; Yejin Zhang (IEEE Photonics Journal)
In this paper, a single emission peak microstructured lasers array for beam control is proposed. And lasers in the array can emit beams in specific directions with low vertical divergence angles. The initial phase control is introduced to solve the problem of multiple emission peaks in a vertical far-field pattern. Both simulation and experimental analyses corroborate that the intensity of high-order diffraction peaks can be suppressed by introducing an appropriate starting position. Experimental results showcase the achievement of a low vertical divergence angle of 0.95° and an expansive angle sweep range of 61.2°. Furthermore, leveraging a taper structure, a horizontal divergence angle of 3.7° and a typical optical output power of 28 mW are obtained.